Kontribusi Kepemimpinan Kepala Sekolah, Sarana Dan Lingkungan Kerja Terhadap Kepuasan Kerja Guru SMP Negeri Di PokJa 02 Kecamatan Boyolali - Chotijah, Siti; , Prof. Abdul Ngalim, MM, M.Hum; , Dr. Suyatmini, M.Si (2015)
The purpose of this research was to analyze the empirical and test hypotheses influence school leadership, facilities and working environment on job satisfaction of teachers SMP in Boyolali District of the Working Group 02. This reseach design using quantitative methods with descriptive approach analysis. Place of junior high school research in the WG 02 N District of Boyolali. Semester 2 year study period 2014. The population is all Junior High School teachers in the District Boyolali 02 Working Group consisting of SMP N 4, 5, and 6 Boyolali some 100 people. The primary data collection techniques in this study, the authors used a technique questionnaires while secondary data obtained through the sources of the document. Data analysis technique begins with the test instrument to test the validity and reliability of the sample teachers do not remain a number of 10 people. Hypothesis Testing with the regression equation, determination (R2), t-test and F. Test results showed leadership variables contributes significantly to job satisfaction of teachers by 13.76%. Variable facilities of contributing significantly to teacher job satisfaction at 8.85% and variable work environment contributes significantly to job satisfaction of teachers by 7.98%. Simultaneously variables of school leadership, facilities and working environment contributes significantly to job satisfaction of teachers by 30.6%